STUDY OF THE RELATIONSHIP BETWEEN THE DEVELOPMENT OF FIBROSIS PROCESSES AND THE FUNCTIONAL STATE OF THE HEART IN PATIENTS WITH CHRONIC HEART FAILURE - Abdigaffar G. Gadaev; Guzel B. Shamsutdinova (International Scientific and Current Research Conferences, 2024)
The development of fibrosis processes in patients with chronic heart failure is correlated with the functional state of the heart. This is also confirmed by positive changes in N-pro-natriuretic peptide and aldosterone indicators after treatments in patients involved in the study, as well as reliable positive improvement in cardiac functional status in those who received sacubitril + valsartan and dapagliflozin. It was demonstrated by highly reliable positive changes in end-systolic and diastolic cardiac volumes and left ventricular ejection fraction.